## Trending News

Promoted

### 2 Answers

Relevance

- llafferLv 71 month ago
This needs a chain rule.

y = (10^x + 10^(-x))²

If we set this up as a chain rule we get:

y = u² and u = 10^x + 10^(-x)

we need the derivative of both so we get:

dy/du = 2u and du/dx = 10^x ln(10) - 10^(-x) ln(10)

Chain rule is:

dy/dx = dy/du * du/dx

substitute and simplify:

dy/dx = 2u * [10^x ln(10) - 10^(-x) ln(10)]

Substitute the u for the expression in terms of x:

dy/dx = 2[10^x + 10^(-x)] * [10^x ln(10) - 10^(-x) ln(10)]

If we factor out the ln(10) we get:

dy/dx = 2 ln(10) [10^x + 10^(-x)] * [10^x - 10^(-x)]

Now we can multiply the two binomials as they are conjugate pairs we should get a 2-term result:

dy/dx = 2 ln(10) [(10^x)² - 10^x * 10^(-x) + 10^x * 10^(-x) - 10^(-x)²]

dy/dx = 2 ln(10) [(10^x)² - 10^(-x)²]

dy/dx = 2 ln(10) [10^(2x) - 10^(-2x)]

Still have questions? Get your answers by asking now.